Unilateral renal agenesis in greater rhea (Rhea americana Linnaeus, 1758) reared under human care in the potiguar semiarid, Brazil - Ana Caroline Freitas Caetano de Sousa; João Augusto Rodrigues Alves Diniz; Igor Renno Guimarães Lopes; Carlos Eduardo Vale Rebouças; Jael Soares Batista; Juliana Fortes Vilarinho Braga; Moacir Franco de Oliveira (Medicina Veterinária)
Considered the largest wild bird in South America, the Greater Rhea is a ratite endowed with great zootechnical value and scientific importance. Understanding the pathologies that may affect these animals is necessary since they are kept in captivity. Thus, seeking effective measures to prevent diseases in livestock is important. The present report aims to describe the first diagnosis of unilateral renal agenesis in Greater Rhea. A male Greater Rhea (Rhea americana) approximately five years old, was euthanized, aiming at the anatomical characterization of the structures that make up the lumbosacral region. Analysis of the coelomic cavity showed the absence of the left kidney and an increase in the volume of the left ureter. The right kidney had normal topography and anatomical structures. Fragments of the right kidney and left ureter were collected, fixed in formaldehyde, and submitted to the inclusion process to obtain histological slides stained by hematoxylin and eosin. The microscopic findings showed no compensatory changes even without the contralateral kidney. The left ureter did not present preserved histological organization. The mucosa was thin due to a large amount of mucoid content in the lumen. In conclusion, unilateral renal agenesis in Greater Rhea is compatible with life. The contralateral kidney is fully functional and can meet the body's demands. In addition, it is important to conduct anatomopathological studies in Greater Rheas under captivity, aiming to expand the understanding of the aspects involved in maintaining this species and the pathologies that affect them.